A COMPARATIVE PROSPECTIVE STUDY LAPAROSCOPIC VERSUS OPEN APPENDICECTOMY IN ADULTS. - Ranjan, Rajani (Student's Journal of Health Research Africa, 2024)
Background A common surgical emergency that typically necessitates an appendicectomy is appendicitis. The decision between laparoscopic and open appendicectomy has generated a lot of discussion, as each procedure has unique benefits and drawbacks. Although laparoscopic surgery is frequently chosen due to its minimally invasive nature, questions still surround its wider applicability, especially in situations of complex appendicitis. Based on several intraoperative and postoperative factors, this study sought to compare laparoscopic versus open appendicectomies. Materials and Methods Two groups of fifty patients undergoing interval appendicectomies were randomly assigned. Twenty-five patients in group A had laparoscopic appendicectomies, while twenty-five patients in group B had open appendicectomies. Results It was simpler to evaluate the intraoperative findings and confirm the diagnosis in group A patients. Furthermore, patients in group A experienced less discomfort, fewer post-operative problems, and a shorter hospital stay. Conclusion Laparoscopic appendicectomy is the preferred method for appendicectomy due to its superior results. Recommendation The authors recommend LA as a routine surgical approach for acute appendicitis.